INTEGRASI TRI KARAKTER MELALUI PAIKEM DI SEKOLAH DASAR NEGERI PONTIANAK BARAT TERAKREDITASI A - Kusumawati, Ayu; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research is to know the integration of Three character (discipline, creative, and responsible) through Paikem in Elementary School Pontianak West Accredited A in terms of planning, realization, and evaluation of learning. The research was conducted in Elementary School 71 Pontianak West and in Elementary School Pontianak West. This research is a descriptive study with a qualitative approach. The subjects in this research is the head of school, teachers, and learners. The data was collected through observation, interviews, and documentation. Data analysis was conducted through phases: data reduction, display data, and with drawal as conclusion. Techniques examination of the data validity using triangulation. The result shows that Three character (discipline, creative, and responsible) through Paikem integrated in planning, implementation and evaluation of the learning already running well. Planning learning characterized by entering the element Paikem and designing lesson. The lesson character already done by applying Learning, Active, Innovative, Creative, Effective, dan fun (PAIKEM) conducted through exemplary teachers and done every day by all citizens of the school. The evaluation learning implemented through assessment authentic, which includes assessment process and assessment learning outcomes.Keywords : integration, three character, paikem